"Effect of Different Saliva Decontamination Procedures on Bond Strength to Dentin in Single Bottle Systems " - M. Ghavam; Sh. Khalaf Pour (Tehran University of Medical Sciences, 2004)
Statement of Problem: Following the increasing use of composites in restoring anterior and posterior teeth, problems due to its technique sensitivity have become a major concern. One of these problems is the possibility of contamination of dentin with saliva, blood and/or gingival fluid in different stages of bonding procedure, even with application of different methods of isolation. However, by introduction of Single-bottle dentin adhesives, the contamination possibility reduced to two stages. Scientific documents show that saliva contamination reduces bond strength of composites to dentin. Application of simple and efficient methods for reducing or eliminating saliva contamination enables clinicians to carry out dental treatment without any concern about deterioration of clinical longevity of restoration. Purpose: This study was designed to compare the effect of different decontamination methods on the shear bond strength of composite to dentin using a "Single-bottle" adhesive. Materials and Methods: Seventy-two extracted sound human molars and premolars were selected. Enamel of buccal surface was ground flat to expose dentin. The teeth were divided into 9 groups of 8 each. In control group (1) the adhesive "Excite" was used according to the manufacturer, without any contamination. Conditioned and saliva contaminated dentin was (2) rinsed and blot dried, (3) rinsed, dried and re-etched. In groups 4, 5, 6 uncured adhesive was saliva contaminated and then: (4) only blot dried (5) rinsed, blot dried with adhesive reapplication and (6) resurfaced with bur, rinsed, dried and followed by repeating the whole process. In groups 7, 8, 9 cured adhesive was contaminated with saliva and then: (7) rinsed and dried (8) rinsed, blot dried with adhesive reapplication (9) same as group (6). Then "Tetric Ceram" composite cylinders were bonded to dentin surfaces. Samples were thermo cycled in 5°C and 55°C water, 30 seconds in each bath with a dowel time of 10 seconds for 500 cycles. Finally, samples were sheared using Instron testing machine and shear bond strength data were subjected to one way ANOVA analysis, and Tukey HSD PostHoc. Mode of failure of samples was examined under Stereomicroscope (×40) and using Log-rank survival data analysis. Results: No statistically difference between mean shear bond strength of groups 1,2,3 was observed (P=0.543). Comparison of groups 4,5,6 with group 1 showed that shear bond strength of group 4 was significantly lower (P